2010
DOI: 10.1007/s11274-010-0358-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel β-mannanase from Pantoea agglomerans A021: gene cloning, expression, purification and characterization

Abstract: This paper describes the construction of a genomic library from the bacterium Pantoea agglomerans A021 and the subsequent cloning and expression of a novel mannanase gene (man26P). The gene consists of 1,047 bp and encodes a peptide (Man26P) of 348 amino acids with a calculated molecular mass of 38.5 kDa. Man26P is 63% identical with mannanase from Pectobacterium carotovorum at protein level and considered to be a member of the glycoside hydrolase family 26 (GH26). Man26P was expressed efficiently in E.coli BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…They reported that the maximum b-mannanase activity was 7.9, 41.1, and 76.1 U/mL, respectively. Wang et al (2010) produced the bmannanase in shake flasks with konjac powder by using Pantoena agglomerans A021 and reported that the maximum b-mannanase activity of purified Man26P was 514 U/mg. It has also been reported that the b-mannanase activity was found to be 2195.5 U/mL in fed-batch bioreactor with corn steep liquor dextrose medium by recombinant Pichia pastoris (Zheng et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…They reported that the maximum b-mannanase activity was 7.9, 41.1, and 76.1 U/mL, respectively. Wang et al (2010) produced the bmannanase in shake flasks with konjac powder by using Pantoena agglomerans A021 and reported that the maximum b-mannanase activity of purified Man26P was 514 U/mg. It has also been reported that the b-mannanase activity was found to be 2195.5 U/mL in fed-batch bioreactor with corn steep liquor dextrose medium by recombinant Pichia pastoris (Zheng et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…A novel mannanase gene ( A021 ) was isolated from marine bacterium Pantoea agglomerans and was cloned in E. coli . Maximum activity of enzyme was observed at pH 6 at 55 o C that enhanced in correlation to the increase of NaCl concentration up to 0.75 M (Wang et al 2010a ).…”
Section: Xylanasesmentioning
confidence: 94%
“…Man1E presented higher expression after IPTG induction for16 h (Fig. 7 e), the mannanase activity was 642.25 U/mL, however, there was no significant difference in soluble expression and activity between 12 and 16 h. By comparison, the optimal inductive temperature and time for Man1E gene expression similar to those of β-mannanase genes from Bacillus circulans NT 6.7 (for 16 h at 18 °C) [ 56 ] and Pantoea agglomerans A021 (for 15 h at 18 °C) [ 57 ]. However, for the expression of three β mannanase genes, the IPTG concentrations were different, which were 0.6 mm, 1.0 mm and 0.05–0.15 mm, respectively.…”
Section: Resultsmentioning
confidence: 99%